Cape Clear Data Interchange 4.7 a solid tool that combines the best of two technologies. - Barbash, Brian
No matter how advanced enterprise systems become, the sophistication of the tools available to build them, or the advances of architectural approaches and best practices from which to start, the life blood of any system is the raw data. Without the data, what's the point? Whether the system is simply collecting information from a set of HTML forms or is one participant in a highly complex, distributed environment consisting of several integration touch points, there will always be the challenge of getting data into and out of the system. Data interchange from Cape Clear provides a novel approach to this problem by applying the best of what XML and Web services have to offer.